If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 = 4 + -3p Solving 28 = 4 + -3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '3p' to each side of the equation. 28 + 3p = 4 + -3p + 3p Combine like terms: -3p + 3p = 0 28 + 3p = 4 + 0 28 + 3p = 4 Add '-28' to each side of the equation. 28 + -28 + 3p = 4 + -28 Combine like terms: 28 + -28 = 0 0 + 3p = 4 + -28 3p = 4 + -28 Combine like terms: 4 + -28 = -24 3p = -24 Divide each side by '3'. p = -8 Simplifying p = -8
| -43-4=7-9x | | x+x+20=200 | | 3p-5=-20 | | 2.4x=8.64 | | 7x^2+16x-15= | | 72-6x=21x+24 | | 7x+1=-35 | | 3x+47=-5 | | 49r(2)+21r=-2 | | 1-6x=-35 | | (2/3)-0,2x=(1/3)-0,5x | | 2c+6=-1-3c | | 70+30=2x | | 3n^2+6n-24=0 | | 5m^2-50m+125=0 | | 6-(1/3)x=2x-3 | | 5(a-8)+14=3(a-6) | | 5m+9=4 | | 5-2x=x+6 | | -6x-3(2x-18)=186 | | -50=5x+4(-3x-2) | | 5x*3y= | | a/2+b/2=c/2 | | 4p^2-4p-48=0 | | -8-9=-3(d+3)-5d | | 2(3x-4)=2(21x+16) | | -5x+2(-2x-11)=-76 | | 2x+3.4=8 | | 2x(3x+1)=28 | | xy+30y-30=0 | | 5x^(1/3)-x^(2/3)-54=0 | | -8r-7=24 |